Dynamic and precise electromagnetic levitation of single cells - Malavika Ramarao; Victor Garcia-Gradilla; Mehmet Burcin Unlu; Ronald W. Davis; Naside Gozde Durmus (Proceedings of the National Academy of Sciences, 2025)
The biophysical properties of single cells are crucial for understanding cellular function and behavior in biology and medicine. However, precise manipulation of cells in 3-D microfluidic environments remains challenging, particularly for heterogeneous populations. Here, we present “Electro-LEV,” a unique platform integrating electromagnetic and magnetic levitation principles for dynamic 3-D control of cell position during separation. We demonstrated that small current adjustments in electromagnets significantly alter the levitation heights of diverse particles and cell types. By periodically modulating and tracking cell positions along the z-axis, Electro-LEV identified distinct levitation behaviors between single cells and cell clusters, with clusters responding more rapidly to magnetic field changes. Furthermore, we demonstrated that Electro-LEV significantly enhances the purity and efficiency of levitational sorting, achieving 10-fold enrichment of live cells from 50% starting viability samples and 18.8-fold enrichment from 10% starting viability samples. These results establish Electro-LEV as a powerful tool for investigating cellular heterogeneity, differentiating cell sizes and types, and improving cell sorting efficiency. Thus, Electro-LEV is broadly applicable, offering different possibilities for high-resolution cell analysis and label-free cell sorting in various biomedical fields, including but not limited to single-cell sequencing and drug screening.